Creativity and interactive solutions in the graphic communications - Szentgyörgyvölgyi, Rozália; Horváth, Csaba; Kovács, György (Univerzita Pardubice, 2013)
The application of traditional forms was common while printed products were dominating the exchange of information. New solutions only emerged gradually. However, competition with electronic communication gave new momentum to creativity in graphic communication. Authors now structure and summarize the needs and expectations that ‘smartphone-using’ consumers have of printed products. They portray creative solutions that were designed to live up to these expectations – solutions that stimulate multiple sensory organs simultaneously and are capable of interactive communication.
Keywords: creative solutions; interactive communication; value added print